NCDs Screening App: PBRI Model for Primary Care - Kesaraporn Choopun; Panarat Chenchob; Suttini Wattanakul; Natpalin Ninpeng; Pleumjit Chotiga (Journal of Health Science and Medical Research, 2026)
Objective: This research study aimed to (1) develop a user-friendly screening application for the identification of individuals at risk for diabetes, hypertension, and depression based on the Praboromarajchanok (PBRI) model; and (2) investigate the prevalence of these conditions among residents in Health Regions 1 and 2 using the developed application.Material and Methods: A two-phase research and development (R&D) design was employed. In Phase 1, the screening application was developed following the five steps of the PBRI model. The app was expert-reviewed and pilot-tested with 30 users. In Phase 2, the app was used to assess the prevalence of diabetes, hypertension, and depression among 420 target participants.Results: The resulting “Non-communicable diseases (NCDs) Screening App” is a web-based tool that incorporates clinical practice guidelines for the target NCDs, and features a seven-color “traffic light” PBRI model for risk level visualization, as well as educational videos and user manuals. Expert evaluations confirmed the high quality of the application, and a high user satisfaction score (4.56±0.19) was obtained by pilot testing. In a larger test sample, the percentage of participants assigned a pale green risk level was highest for hypertension (37.14%), followed by depression (32.38%) and diabetes (22.62%). Overall, user satisfaction during NCD prevalence screening was also high (4.34±0.41).Conclusion: The PBRI-based NCDs Screening App has significant potential as a digital tool for early detection and health promotion in primary care settings. It supports the work of village healthcare volunteers and healthcare providers in proactive, community-based screening and education.